The Rules of Asasiyah Al-Umur bi Maqasidiha in Islamic Law - Ruri Aldisyah Siregar; Muhammad Irfan Luthfi Damanik; Sofia Ramadhani Purba; Azan Subuh Mustafa Lubis (Jurnal Cendikia ISNU SU, 2025)
The rule of asasiyah al-umur bi maqasidiha is one of the fundamental principles in Islamic law which emphasizes that every legal act is judged based on the purpose and intention behind it. In the context of modern society faced with the complexity of legal and ethical issues, this rule is an important instrument in answering contemporary problems that are not explicitly regulated in the nash. This article aims to comprehensively examine the formulation of the principles of asasiyah al-umūr bi maqāṣidihā, its normative foundations in the Qur'an and Hadith, the branches of the rules that are born from them, and the scope of their application in contemporary Islamic law. This research uses a descriptive qualitative method with a normative approach, through the analysis of fiqh literature, ushul fiqh, and the works of classical and contemporary scholars. The results of the study show that the rules of al-umūr bi maqāṣidihā have a strategic role in the establishment of Islamic law that is oriented towards substantive justice and benefits, especially in issues such as sharia economics, social activities, and individual rights. In conclusion, this rule not only serves as a methodological guideline in ijtihad, but also as a means of actualizing the values of maqāṣid al-syarī'ah in the face of the dynamics of law and the life of modern society.